Garment Therapy does not Improve Function in Children with Cerebral Palsy: A Systematic Review. (8th August 2018) - Wells, Hannah; Marquez, Jodie; Wakely, Luke
ABSTRACT: Aims : To conduct a systematic review asking, does garment therapy improve motor function in children with cerebral palsy? Methods : A systematic review with meta-analysis was conducted to review the literature. Inclusion criteria involved the wearing of therapy suits/garments in children with cerebral palsy. The primary outcome of interest was movement related function and secondary outcomes included impairment, participation, parental satisfaction and adverse outcomes of garment wear. Results : 14 studies with 234 participants were included, of which 5 studies were included for meta-analysis. Garment therapy showed a nonsignificant effect on post-intervention function as measured by the Gross Motor Function Measure when compared to controls (MD = −1.9; 95% CI = −6.84, 3.05). Nonsignificant improvements in function were seen long-term (MD = −3.13; 95% CI = −7.57, 1.31). Garment therapy showed a significant improvement in proximal kinematics (MD = −5.02; 95% CI = −7.28, −2.76), however significant improvements were not demonstrated in distal kinematics (MD = −0.79; 95% CI = −3.08, 1.49). Conclusions : This review suggests garment therapy does not improve function in children with cerebral palsy. While garment therapy was shown to improve proximal stability, this benefit must be considered functionally and consider difficulties associated with garment use.